2022
DOI: 10.3390/ijerph192114599
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Safety Performance of Construction Workers through Individual Perception and Organizational Collectivity: A Contrastive Research between Mainland China and Hong Kong

Abstract: Considering the increasing number in construction accidents in Mainland China and Hong Kong, research on improving the safety performance of construction personnel is important, given the essential role it plays in occupational safety development in industries. The present study aimed to assess the improving channels of safety performance through individual perception and organizational collectivity in a quantitative way by integrating safety motivation as the transition role between individual and organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Although it is commonly documented that more experienced and well-educated individuals perform better in terms of safety [36][37][38], some earlier works revealed that there are still doubts about the role of educational level. Diaz and Cabrera pointed out that worker safety attitude and performance are not significantly associated with educational level, implying that a higher educational level does not imply greater worker safety [39].…”
Section: Safety Performance Affected By the Educational Levels Of Wor...mentioning
confidence: 99%
“…Although it is commonly documented that more experienced and well-educated individuals perform better in terms of safety [36][37][38], some earlier works revealed that there are still doubts about the role of educational level. Diaz and Cabrera pointed out that worker safety attitude and performance are not significantly associated with educational level, implying that a higher educational level does not imply greater worker safety [39].…”
Section: Safety Performance Affected By the Educational Levels Of Wor...mentioning
confidence: 99%